Lexis of Latvian-speaking Communities at the Baltic Sea Coast in Latvia and Lithuania: Denominations of the Object kitchen - Rudzāte, Ilze (Acta humanitarica academiae Saulensis, 2023)
Until now, little attention has been paid to studies of Latvian language vocabulary on a thematic aspect related to the traditional homestead on the Baltic Sea coast once inhabited by the Curonians. This article presents names denominating the object of a kitchen in a traditionally built dwelling house, their diversity, origins, and prevalence in Latvian-speaking communities on the coast of the Baltic Sea in Latvia and Lithuania. The analysis is based on Latvian material from various written sources, using descriptive, partly historical and mapping methods. The vocabulary analysed in the sources of this article shows lexemes that denominate both the separate, enclosed room and the part of the room used for food preparation and cooking. The prevalence of analysed lexemes in the meaning of a ‘kitchen’ is not uniform. In the coastal areas of Kurzeme, the names ķēķis, kukņa, plītsistaba, virtuve and their variations were identified, but in the vocabulary of the Latvian dialect of Šventoji, the morphological variant ķēķe inherited from the dialectal vocabulary of Kurzeme has been recorded. In the vocabulary of Kurzeme, names denominating a kitchen are mainly of Germanic and Slavic origin. The emergence of Germanisms in the Latvian vocabulary related to the kitchen is directly related to the material cultural peculiarities, which were encouraged to Latvian peasants in Kurzeme by the German nobility, and to the Baltic German everyday speech. The impact of Lithuanian as an intermediary language has been recorded mainly in the Latvian dialect of the Curonian Spit. The borrowed names with the meaning of a ‘kitchen’, such as kukne || kukine, can be explained by the close contact of New Curonians with the Lithuanian-speaking community on the eastern coast of the Curonian Lagoon; New Curonians not only had economic ties with them, but also formed mixed families.
Keywords: Latvian; lexis; architecture; kitchen; semantics; language contacts